Senolytic and senomorphic secondary metabolites as therapeutic agents in Drosophila melanogaster models of Parkinson’s disease - Miller, Sean J.; Darji, Rayyan Y.; Walaieh, Sami; Lewis, Jhemerial A.; Logan, Robert (Frontiers in Neurology, 2023)
Drosophila melanogaster is a valuable model organism for a wide range of biological exploration. The well-known advantages of D. melanogaster include its relatively simple biology, the ease with which it is genetically modified, the relatively low financial and time costs associated with their short gestation and life cycles, and the large number of offspring they produce per generation. D. melanogaster has facilitated the discovery of many significant insights into the pathology of Parkinson’s disease (PD) and has served as an excellent preclinical model of PD-related therapeutic discovery. In this review, we provide an overview of the major D. melanogaster models of PD, each of which provide unique insights into PD-relevant pathology and therapeutic targets. These models are discussed in the context of their past, current, and future potential use for studying the utility of secondary metabolites as therapeutic agents in PD. Over the last decade, senolytics have garnered an exponential interest in their ability to mitigate a broad spectrum of diseases, including PD. Therefore, an emphasis is placed on the senolytic and senomorphic properties of secondary metabolites. It is expected that D. melanogaster will continue to be critical in the effort to understand and improve treatment of PD, including their involvement in translational studies focused on secondary metabolites.